REPRESENTASI BUDAYA PATRIARKI PADA FILM POSESIF (ANALISIS SEMIOTIKA ROLAND BARTHES) - Ganesa Aditya (2022)
The patriarchal culture shown in the film "Possessive" is a picture of the life of a phenomenon that is happening today. This has a detrimental impact on women in various aspects of life. This study aims to determine the meaning of patriarchy shown in the film "Possessive" using Roland Barthes' semiotic theory which has three meanings in researching it, namely denotation, connotation, and myth. The research method used is semiotic analysis from Roland Barthes using primary and secondary data sources. The data collection technique was carried out with a documentation study technique where the research object was taken from the "Possessive" movie scene. The data obtained were then analyzed using the semiotic analysis of Roland Barthes. The results of this study indicate that the meaning of patriarchy in the film "Posessive" is more highlighted by violence against women. Violence is a form of patriarchy in the public sphere.